Is encopresis always the result of constipation? - Benninga, M A (1994)
Encopresis is often the result of chronic constipation in the majority of paediatric patients. In clinical practice, however, encopresis is also seen without constipation and it is unknown whether these two clinical variants are based on similar or different pathophysiological mechanisms, requiring different therapeutic approaches. We analysed clinical symptoms, colonic transit time (CTT), orocaecal transit time (OCTT), anorectal manometric profiles, and behavioural scores. Patients were divided into two groups, one consisted of 111 children with paediatric constipation, and another group of 50 children with encopresis and/or soiling without constipation. Significant clinical differences in children with encopresis/soiling existed compared with children with paediatric constipation regarding: bowel movements per week, the number of daytime soiling episodes, the presence of night time soiling, the presence and number of encopresis episodes, normal stools, pain during defecation, abdominal pain, and good appetite. Total and segmental CTT were significantly prolonged in paediatric constipation compared with encopresis/soiling, 62.4 (3.6-384) and 40.2 (10.8-104.4) hours, respectively. No significant differences were found in OCTT. Among the two groups, all manometric parameters were comparable, except for a significantly higher threshold of sensation in children with paediatric constipation. The defecation dynamics were abnormal in 59% and 46% in paediatric constipation and encopresis/soiling, respectively, and were significantly different from controls. Using the child behaviour checklist no significant differences were found when comparing children with paediatric constipation and encopresis/soiling, while both patient groups differed significantly from controls. In conclusion, our findings support the concept of the existence of encopresis as a distinct entity in children with defecation disorders. Identification of such children is based on clinical symptoms, that is, normal defecation frequency, absence of abdominal or rectal palpable mass, in combination with normal marker studies and normal anal manometric threshold of sensation, Thus, encopresis is not always the result of constipation and can be the only clinical presentation of a defecation disorder.